EPIDEMIOLOGY OF ISCHEMIC HEART DISEASE - Vujcic, Isidora; Maksimovic, Jadranka; Sipetic Grujicic, Sandra (Medical Research, 2025)
Ischemic heart disease (IHD), or coronary artery disease, ranks as the primary global cause of mortality and disability. This narrative review summarizes the epidemiology of IHD, focusing on global distribution, risk factors, and prevention. A literature search was conducted using PubMed, Scopus, and Google Scholar databases to identify relevant studies from the past decade. In 2019, IHD affected 197.2 million individuals, resulting in 9.1 million deaths, and 182.0 million disability-adjusted life years (DALYs) worldwide. While age-standardized mortality rates, DALYs, and prevalence have declined, the number of reported cases continues to rise. The highest prevalence was reported in Central and Eastern Europe and Central Asia, while the lowest was in South Asia. Modifiable and non-modifiable risk factors influence IHD. The main causal risk factors, such as hypertension, dyslipidemia, diabetes, smoking, and age, are independently associated with IHD development. Environmental factors (air pollution, noise exposure, and climate change) further increase the risk of IHD. The emerging concept of the exposome emphasizes that the cumulative and combined influence of environmental risk factors plays a crucial role in the development of IHD. IHD can be prevented from developing through primordial (targeting social determinants like urbanization, poverty, illiteracy, living conditions) and primary prevention (management of risk factors through lifestyle interventions, pharmacotherapies). IHD is a growing global health and economic challenge, disproportionately affecting low-income regions, as a result of population aging, limited access to healthcare, and the presence of numerous risk factors that require appropriate prevention and treatment.